2014
DOI: 10.1007/s11182-014-0283-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Energy Characteristics of Metallized Mixed Compositions Based on a Binary Oxidizer at Increased Pressures

Abstract: Results of a thermodynamic calculation of the energy characteristics for mixed compositions containing aluminum powder are presented. The influence of the aluminum content in the mixed compositions on the adiabatic combustion temperature, specific impulse, and composition of the combustion products is considered. Results of an experimental study of combustion of metallized mixed compositions in the pressure range from 0.1 to 6 MPa are presented. The effect of the aluminum powder dispersity and the relative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…As far as metal powders are concerned, aluminum is of greatest interest as a consequence of the low melting temperature of pure aluminum and its oxide (in comparison with magnesium, zirconium, and beryllium), its availability, acceptable cost, and high heat release when burned with oxygen [1]. In [2][3][4][5][6] it was shown that the introduction of aluminum nanopowder (nAl) into the makeup of solid MC makes it possible to significantly increase the burning rate, decrease the ignition delay time, increase the completeness of aluminum combustion, and decrease the loss of specific impulse.…”
Section: Introductionmentioning
confidence: 99%
“…As far as metal powders are concerned, aluminum is of greatest interest as a consequence of the low melting temperature of pure aluminum and its oxide (in comparison with magnesium, zirconium, and beryllium), its availability, acceptable cost, and high heat release when burned with oxygen [1]. In [2][3][4][5][6] it was shown that the introduction of aluminum nanopowder (nAl) into the makeup of solid MC makes it possible to significantly increase the burning rate, decrease the ignition delay time, increase the completeness of aluminum combustion, and decrease the loss of specific impulse.…”
Section: Introductionmentioning
confidence: 99%